CIVIC ENGAGEMENT AND OLDER ADULTS’ SUPPORT FOR COMMUNITY- DRIVEN DEVELOPMENT: A STUDY OF ORON AND UDUNG UKO LOCAL GOVERNMENT AREAS IN AKWA IBOM STATE, NIGERIA - NKPOYEN, FESTUS; GLORY ETENG, BASSEY (IJRDO - Journal of Social Science and Humanities Research, 2017)
The study assessed the relationship between civic engagement and older adults ‘support for community-driven development. The specific research purposes were: To demonstrate how civic engagement through involvement in decision making at village committee relates with older adults’ support for community –driven development, to examine whether civic engagement through mobilization of information resource relates to older adults’ support for community-driven development, to determine whether civic engagement through building social capital by consulting relates to older adults’ support for community –driven development and finally, to disseminate research findings to the widest possible audience of policy makers, non-Governmental Organizations (NGOs) and academics. It was hypothesized that involvement in village committee decision making process, mobilization of information resource and building social capital by consulting do not significantly relate with older adults’ support for community-driven development. The study addressed gaps in the current literature about civic engagement and community development implications for older adults. The importance laid in expanding the understanding of civic engagement and the potential of the aged participating in community life and bringing life experience to civic life. The research methodology was a case study analysis with survey design. Primary data were obtained from structured interviews conducted with 160 older adults from 1o villages in the study area. Key findings of the study revealed that civic engagement by older adults helps to tap their energies and resources within the community. It was concluded that civic engagement has a positive impact on older adults’ support for community-driven development. The implication is that civic engagement is an important instrument for grassroot sustained development.